Oral Nano Vitamin D Supplementation Reduces Disease Activity in Ulcerative Colitis: A Double-Blind Randomized Parallel Group Placebo-controlled Trial. Issue 10 (November 2019) - Ahamed Z, Rizwan; Dutta, Usha; Sharma, Vishal; Prasad, Kaushal Kishor; Popli, Priyanka; Kalsi, Dimple; Vaishnavi, Chetana; Arora, Sunil; Kochhar, Rakesh
Abstract : Introduction: Vitamin D possesses anti-inflammatory properties and could be beneficial in ulcerative colitis (UC). Methods: We studied the effect of oral nano vitamin D3 supplementation on disease activity in active UC [ulcerative colitis disease activity index (UCDAI)≥3]. Patients with active UC and vitamin D <40 ng/mL were randomized to receive either oral nano vitamin D (60, 000 IU/d×8 d) or placebo. They were evaluated for disease activity (UCDAI scores, C-reactive protein, erythrocyte sedimentation rate, and fecal calprotectin) at baseline and reassessed at 4 weeks. The response was defined as a 3-point reduction in UCDAI score at 4 weeks and reduction in inflammatory markers. Results: The median vitamin D levels increased from 15.4 to 40.83 mg/dL in vitamin D group ( P ⩽0.001) and marginally from 13.45 to 18.85 mg/dL ( P =0.027) in controls. The 3-point reduction in UCDAI was seen more often in vitamin D group as compared with the control (53% vs. 13%; P =0.001). Increase in vitamin D levels correlated with reduction in UCDAI score ( P⩽ 0.001; ρ=−0.713), C-reactive protein ( P⩽ 0.001; ρ=−0.603), and calprotectin ( P =0.004; ρ=−0.368). Patients who achieved target vitamin D of >40 ng/mL (n=17) more often had a 3-point reduction in UCDAI (80% vs. 20%; P⩽ 0.001) and reduction in grade of severity from 60% to 35% ( P =0.038). Vitamin D administration (odds ratio, 9.17; 95% confidence interval, 2.02-41.67) and baseline histologic activity (odds ratio, 1.92; 95% confidence intervals, 1.2-3.08) independently predicted response. Conclusions: Oral nano vitamin D supplementation in active UC is associated with a reduction in disease activity and severity grade and is seen more often in those who achieved a target vitamin D level of 40 ng/mL. Abstract : Supplemental Digital Content is available in the text.